Does Financing Decision-Making by Regional Government-Owned Syariah Banks Depend on Financial-Information Quality and Managers' Characteristic? - Eka Hasnita Putri; Yossi Diantimala; Mulia Saputra (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study examines the impact of financial information quality on managers’ financing decision-making. It also investigates the role of managers’ characteristics – educational background, gender, and working period – on the relationship between the quality of financial statement information and financing decision-making. The samples were finance managers at Bank Aceh Syariah, a Syariah bank owned by the regional government in Aceh, consisting of 24 finance managers at the branch offices and 86 finance managers at sub-branches that spread throughout Aceh. The data was obtained by using a questionnaire distributed using google form. A multivariate analysis was used to test the hypothesis. The results showed that the quality of financial statement information has a positive effect on financing decisions. It becomes the basis for managers in making financing decisions in Islamic banks owned by local governments. Managers’ characteristics do not influence financing decisions and do not strengthen or weaken managers in making financing decisions based on financial statements. The result confirms hypothesis 1, however, it does not support any other hypotheses regarding finance managers’ characteristics. Therefore, it is suggested for future research to broaden and compare the characteristics of finance managers of national Islamic banks in Indonesia and Islamic banks from other countries to capture comprehensive results.